Basics for performing a high-quality color Doppler sonography of the vascular access. Issue 1 (November 2021) - Meola, Mario; Ibeas, Jose; Lasalle, Gianfranco; Petrucci, Ilaria
In the last years, the systematic use of ultrasound mapping of the upper limb vascular network before the arteriovenous fistula (AVF) implantation, access maturation, and clinical management of late complications is widespread and expanding. Therefore, a good knowledge of theoretical outlines, instrumentation, and operative settings is undoubtedly required for a thorough examination. In this review, the essential Doppler parameters, B-Mode setting, and Doppler applications are considered. Basic concepts on the Doppler shift equation, angle correction, settings on pulse repetition frequency, operative Doppler frequency, gain are reported to ensure adequate and correct sampling of blood flow velocity. A brief analysis of the Doppler inherent artefacts (as random noise, blooming, aliasing, and motion artefacts) and the adjustment setting to minimize or eliminate the confounding artefacts are also considered. Doppler aliasing occurs when the pulse repetition frequency is set too low. This artefact is particularly frequent in vascular access sampling due to the high velocities range registered in the fistula's different segments. Aliasing should be recognized because its correction is crucial to analyse the Doppler signals correctly. Recent advances in instrumentation are also considered about a potential purchase of a portable ultrasound machine or a top-of-line, high-end, or mid-range ultrasound system. Last, the pulse wave Doppler setting for vascular access B-Mode and Doppler assessment is summarized.